Copulatory Mechanics Reveals a Self‐Bracing Mechanism via a Femoral Apophysis in Funnel Weavers (Araneae, Agelenidae) - Zamani, Alireza; Kaya, Rahşen S.; Kaunisto, Kari; Michalik, Peter (Wiley, 2025)
Spiders utilize an indirect method of sperm transfer via specialized male palpal structures. In entelegyne spiders, these structures exhibit a remarkable complexity, comprising various sclerites that interlock with the female genitalia to provide stability and facilitate sperm transfer. Among the four primary coupling mechanisms recognized in entelegyne spiders, one, termed self-bracing, involves interactions between structures stabilizing the expanded copulatory organ during mating. Such interactions can involve elements that are not part of the copulatory organ. The retrolateral tibial apophysis (RTA), a characteristic of the largest group of spiders (RTA clade), is the most prominent structure for this purpose. However, recent research has demonstrated that in spiders that have lost the RTA, other parts of the palp, specifically femoral apophyses, can be involved in self-bracing. The presence of a femoral palpal fapophysis is uncommon in spiders, and only a few taxa possess apophyses on multiple palpal articles, i.e., tibia and femur, the interaction and evolution of which remain to be elucidated. This study investigated the function and interaction of apophyses on different palpal structures for the first time using the funnel weaver Anatextrix monstrabilis (Agelenidae). We specifically examined the hypothesis that the various prominent femoral apophyses are involved in self-bracing despite the presence of an RTA. Micro-computed tomography data of a cryofixed mating pair revealed that at least one of these apophyses functions in self-bracing by fitting into the groove of the embolic base, representing the second documented case of this unique self-bracing mechanism in entelegyne spiders. Furthermore, scanning electron microscopy revealed previously undocumented features in the female genitalia of Anatextrix, including an epigynal fovea, an anterior hood, and well-developed epigynal lateral margins, which potentially play a role in interlocking with male palpal sclerites during copulation. In contrast to ghost spiders (Anyphaenidae), the only other known group of entelegyne spiders exhibiting self-bracing with femoral apophyses, Anatextrix species demonstrate notable differences with regard to the size and shape of these apophyses. Thus, our study indicates that male palpal femoral structures, which do not contact female genitalia during genital coupling, can be subject to strong selection pressures similar to somatic structures that function beyond basic sperm transfer.